Gestión de procompite y el desarrollo competitivo de los productores de la región Loreto 2022 - Ramírez del Aguila, Rosa Behti (2023)
An investigation was carried out in order to determine the relationship between procompite management and the competitive development of producers in the Loreto 2022 Region. The study was descriptive and correlational, where the collected data were analyzed and described. In addition, it was a non-experimental design, the variables were not manipulated. The study population consisted of 1030 producers, of which 280 were selected to carry out a survey accompanied by a questionnaire to collect data. Obtaining the following results, the management of procompite is perceived as regular by 27%, since the program sometimes provides them with infrastructure, work equipment, supplies or materials for their productive activity. Regarding competitive development, it was perceived as regular by 28%, given that they sometimes use sales strategies to enter new markets. Finally, it was concluded that it has been concluded that there is a significant relationship between procompite management and competitive development, information that has been corroborated by the correlation coefficient of 0.832, which is considerable positive and has a significance (bilateral) at level 0.01. Likewise, a positive relationship is established between the dimension phase of authorization (r = 0.716; p = 0.000) and the phase of execution (r = 0.764; p = 0.000), and the dimension phase of implementation obtained a correlation coefficient of 0.705, which is positive average, with the competitive development.